MO443EFFECTS OF SHORT-TERM POTASSIUM CHLORIDE SUPPLEMENTATION IN PATIENTS WITH CHRONIC KIDNEY DISEASE*. (29th May 2021) - Gritter, Martin; Wouda, Rosa; Yeung, Stanley Ming Hol; Vogt, Liffert; De Borst, Martin; Rotmans, Joris; Hoorn, Ewout
Abstract: Background and Aims: A high potassium (K + ) diet is part of a healthy lifestyle and reduces blood pressure. Indeed, salt substitution (replacing NaCl by KCl) reduces the incidence of hypertension. Furthermore, emerging data show that high urinary K + excretion in patients with chronic kidney disease (CKD) is associated with better kidney outcomes. This suggests that higher dietary K + intake is also beneficial for patients with CKD, but a potential concern is hyperkalemia. Thus, there is a need for data on the effects of KCl supplementation in patients with CKD. Methods: The effect of KCl supplementation (40 mEq/day) was studied by analyzing the 2-week open-label run-in phase of an ongoing randomized clinical trial studying the renoprotective effects of 2-year K + supplementation in patients with progressive CKD and hypertension. The aims were to (1) analyze the effects of KCl supplementation on whole-blood K + (WBK + ) and acid-base balance, (2) identify factors associated with a rise in WBK +, and (3) identify risk factors for hyperkalemia (WBK + > 5.5 mEq/L) . Results: In 200 patients (68 ± 11 years, 74% males, eGFR 32 ± 9 mL/min/1.73 m 2, 84% on renin-angiotensin inhibitors, 39% with diabetes mellitus), KCl supplementation increased urinary K + excretion from 73 ± 24 to 106 ± 29 mEq/day, urinary chloride excretion from 144 ± 63 to 174 ± 60 mEq/day, WBK + from 4.3 ± 0.5 to 4.7 ± 0.6 mEq/L, and plasma aldosterone from 294 to 366 ng/L (P < 0.01 for all). Plasma chloride increased from 104 ± 4 to 106 ± 4 mEq/L, while plasma bicarbonate decreased from 24.4 ± 3.4 to 23.6 ± 3.5 mEq/L and venous pH from 7.36 ± 0.03 to 7.34 ± 0.04 (P < 0.001 for all); urinary ammonium excretion did not increase (stable at 17.2 mEq/day). KCl supplementation had no significant effect on plasma renin (33 to 39 pg/mL), urinary sodium excretion (156 ± 63 to 155 ± 65 mEq/day), systolic blood pressure (134 ± 16 to 133 ± 17 mm Hg), eGFR (32 ± 9 to 31 ± 8 mL/min/1.73 m 2 ) or albuminuria (stable at 0.2 g/day). Multivariable linear regression identified that age, female sex, and renin-angiotensin inhibitor use were associated with an increase in WBK +, while diuretic use, baseline WBK +, and baseline bicarbonate were inversely associated with a change in WBK + after KCl supplementation (Table 1 ). The majority of patients (n = 181, 91%) remained normokalemic (WBK + 4.6 ± 0.4 mEq/L). The 19 patients who did develop hyperkalemia (WBK + 5.9 ± 0.4 mEq/L) were older (75 ± 8 vs. 67 ± 11 years), had lower eGFR (24 ± 8 vs. 32 ± 8 mL/min/1.73 m 2 ), lower baseline bicarbonate (22.3 ± 3.6 vs. 24.6 ± 3.3 mEq/L), higher baseline WBK + (4.8 ± 0.4 vs. 4.2 ± 0.4 mEq/L), and lower baseline urinary K + excretion (64 ± 16 vs. 73 ± 25 mEq/day, P < 0.05 for all). Conclusions: The majority of patients with advanced CKD remains normokalemic upon KCl supplementation, despite low eGFR, diabetes mellitus, or the use of renin-angiotensin inhibitors. This short-term study illustrates the feasibility of investigating the renoprotective potential of increased K + intake or KCl-enriched salt in patients with CKD and provides the characteristics of patients in whom this is safe. Our study also shows that KCl supplementation causes a tendency towards metabolic acidosis, possibly by preventing an increase in ammoniagenesis. Longer-term studies are required to study the anti-hypertensive and renoprotective potential of K + supplementation.